EKOSISTEM PENDIDIKAN DAN PENGARUHNYA TERHADAP KEMATANGAN EMOSI SISWA DI SMA NEGERI 1 MUARO JAMBI - Helmi Helmi (Universitas Batanghari Jambi, 2018)
Abstract: Theaims of this study areto find out: 1) the influence of educational ecosystem on the students' emotional maturity 2) the influence of family education on the students' emotional maturity 3) the influence of school education on the students' emotional maturity, and 4) the influence of public education on the students' emotional maturity. This research was correlational research with quantitative approach. This research used a survey method with a questionnaire, which contained a series of questions about a problem or field to be studied. The sample comprised of 47 students, which were randomly taken from the Class XII IPA as the population. The data analysis used simple linear regression analysis. The result revealedthat there was the correlation between the educational ecosystem and the students' emotional maturity. From the result of the data, family education was the most influencingfactor on the students' emotional maturity in the school. Itwas around 12.72% students in the low category but sure. Mean while, the result of the school education was almost the same as theresult of public education.Both were in the lower effect on the students' emotional maturity in SMA Negeri 1 Muaro Jambi. They were around 7.43% and 7.15% studentsin a low category but defined.Keywords: Educational Ecosystems, Emotional Maturity